Safety of venomenhal venom in maintenance Hymenoptera venom immunotherapy - Košnik, Mitja (Zdravniški vestnik, 2001)
Background. Venomenhal (V) is a new brand of Hymenoptera venom allergen for diagnosis and immunotherapy of venom allergy. We studied the safety of switching the patients treated with other brands of venom to V Methods. We performed duplicate skin prick tests with V and ALK Reless (R) venomextract (100microg/ml) in 68 patients (50 males, 42 +- 15 years) on maintenance immunotherapy with honey bee (26) or wasp (42) venom. On two consecutive maintenance injection days 53 patients received in random order either 100 microg of R or V venom. Results. Weal diameter in skin prick tests (mean +- st. dev.) were 3.9 +- 1.1 mm (V) and 4.1 t 1.0 mm (R) for bee venom (NS) and 3.4 +- 1.0 mm (V) and 3.9 +- L2 mm (R) for wasp venom (p < 0.01). Local reaction 30 minutes after maintenance injection were 61 t 1. 7 em (V) and 54 +- 2:5 cm (R) for bee venom (NS)-and5.1 +-1.8cm (V) and 6.1 +- 1.8cm (R) for wasp venom (p < 0.05). Late local reactions (LLR) and tiredness (T) on the dayof injection and 24 hours after injection were equally distributed among both groups and were mild (LLR on the day of injection: 38% of patients (V) vs. 43 % (R). LLR after 24 hours: 28% (V) vs. 28% (R) T on the day of injection: 21 % (V) vs. 23 % (R). T after 24 hours: 0% (V) vs. 6% (R). Conclusions. V was at least as safe as A. There were no adverse reactions due to switching from one brand to another. Slightly but significantly smaller weal in skin prick tests and immediate local reactions might be due to lesser potency or better purification of V wasp extract.
Keywords: Alergeni; alergija; Allergens; Arthropoda, strupi; Bee venoms; Desensitization, immunologic; Desenzibilizacija imunološka; Hymenoptera; imunologija; imunoterapija; Intradermal tests; Intradermalni testi; therapy; Wasp venoms; zdravljenje